Tris(4-methylanilinium) pentachloridoantimonate(III) chloride monohydrate - Qian Xu (Acta Crystallographica Section E, 2012)
The title compound, (C7H10N)3[SbCl5]Cl·H2O, consists of 4-methylanilinium cations, Cl− and [SbCl5]2− anions and water molecules. The five Cl atoms bound to Sb [Sb—Cl = 2.4043 (9)–2.6262 (11) Å] form a square-pyramidal coordination environment. In addition, two [SbCl5]2− anions related by an inversion center are joined by Sb...Cl interactions [Sb...Cl = 3.7273 (14) Å] into an [Sb2Cl10]4− dimer with two bridging Cl atoms. The anions, water molecules and ammonium groups of the cations are linked by N—H...Cl, N—H...O and O—H...Cl hydrogen bonds, forming layers parallel to the ac plane. The benzene rings of the 4-methylanilinium cations are packed between these layers.